2014
DOI: 10.1039/c4cc03158j
|View full text |Cite
|
Sign up to set email alerts
|

Construction of supramolecular hyperbranched polymers via the “tweezering directed self-assembly” strategy

Abstract: A bis-alkynylplatinum(II) terpyridine tweezer-alkynylgold(III) diphenylpyridine guest is shown to maintain the specific complexation in the presence of a B21C7-secondary ammonium salt recognition motif, which facilitates the formation of supramolecular hyperbranched polymers via the "tweezering directed self-assembly" strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…An interesting example comes from Wang et al, who constructed supramolecular hyperbranched polymers via a "tweezering-directed self-assembly" strategy, combining the inclusion mode from a crown ether−guest system and the tweezering mode from a tweezer-like molecule (Figure 40). 233 It was shown that a bis[alkynylplatium(II) terpyridine] tweezer, 66, could clamp an alkynylgold(III) diphenylpyridine guest, 67, leading to the formation of a supramolecular A 2 monomer terminated by a crown ether. After the addition of a B 3 secondary ammonium salt monomer, 68, a supramolecular hyperbranched polymer containing two kinds of binding modes was successfully constructed.…”
Section: Supramolecular Hyperbranched Polymersmentioning
confidence: 99%
“…An interesting example comes from Wang et al, who constructed supramolecular hyperbranched polymers via a "tweezering-directed self-assembly" strategy, combining the inclusion mode from a crown ether−guest system and the tweezering mode from a tweezer-like molecule (Figure 40). 233 It was shown that a bis[alkynylplatium(II) terpyridine] tweezer, 66, could clamp an alkynylgold(III) diphenylpyridine guest, 67, leading to the formation of a supramolecular A 2 monomer terminated by a crown ether. After the addition of a B 3 secondary ammonium salt monomer, 68, a supramolecular hyperbranched polymer containing two kinds of binding modes was successfully constructed.…”
Section: Supramolecular Hyperbranched Polymersmentioning
confidence: 99%
“…A new type of dynamic covalent macrocycle with self-promoted supramolecular gelation behavior is developed. Under oxidative conditions, the dithiol compound containing a diamide alkyl linker with an odd number (7) of carbon chain and an appended crown ether shows a remarkable gelation ability in acetonitrile, without any template molecules. Due to the existence of crown ethers and disulfide bonds, the obtained gel shows a multiple stimuliresponsiveness behavior.…”
Section: Macrocyclic Gelsmentioning
confidence: 99%
“…Therefore, the integration of selective molecular recognition units into the gelator molecules or their fibrous structures provides abundant opportunities to create specific responses or to develop multiple stimuli‐responsiveness, self‐healing, and shape‐memory . To date, various non‐covalent recognition interactions have been employed to build these fascinating soft materials, including hydrogen bonding, π–π stacking, van der Waals, coordination, electrostatic, and host–guest interactions . Macrocycles, including crown ethers, cyclodextrins, calixarenes, and cucurbiturils and pillararene have been widely utilized in the fabrication of supramolecular gels via host–guest interactions as driving force.…”
mentioning
confidence: 99%
“…The propensity of self-assembly extended to create hierarchical supramolecular polymer architectures has attracted increasing interest recently. [1][2][3][4][5][6] Self-assembled polymer architecture reects the integrated structural and functional features of monomer components. The self-assembly mechanism is an autonomous molecular organization with high geometric precision and it is strongly governed by the cooperative multiple non-covalent interactions.…”
Section: Introductionmentioning
confidence: 99%